Food-derived multifunctional bioactive proteins and peptides: Applications and recent advances - Agyei, D.; Potumarthi, R.; Danquah, Michael (2015)
© 2015 by John Wiley & Sons, Ltd. All rights reserved. Owing to their biological roles, multifunctional peptides constitute a new generation of biologically active molecules whose potential can be exploited in several industrial applications such as functional food, pharmaceutical, and cosmeceutical industries. With the required combination and balance of research and commercial operations, major corporations can effectively harness the diverse functionalities of these peptides for enhanced nutrition and the treatment and mitigation of ill health. However, further insightful research in vivo and clinical studies are needed to unravel the mechanism and fate of these peptides en route to the body systems. This is needed to firmly establish the therapeutic potency of these peptides.